Pressure-driven phase transitions and reduction of dimensionality in 2D silicon nanosheets. Issue 1 (December 2018) - Hwang, Gil; Blom, Douglas; Vogt, Thomas; Lee, Jaejun; Choi, Heon-Jin; Shao, Sen; Ma, Yanming; Lee, Yongjae
Abstract In-situ high-pressure synchrotron X-ray powder diffraction studies up to 21 GPa of CVD-grown silicon 2D-nanosheets establish that the structural phase transitions depend on size and shape. For sizes between 9.3(7) nm and 15.2(8) nm we observe an irreversible phase transition sequence from I (cubic) → II (tetragonal) → V (hexagonal) during pressure increase and during decompression below 8 GPa the emergence of an X-ray amorphous phase. High-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) and atomic force microscopy (AFM) images of this X-ray amorphous phase reveal the formation of significant numbers of 1D nanowires with aspect ratios > 10, which are twinned and grow along the <111> direction. We discovered a reduction of dimensionality under pressure from a 2D morphology to a 1D wire in a material with a diamond structure. MD simulations indicate the reduction of thermal conductivity in such nanowires. Silicon nanostructures have important applications as functional materials. Here the authors investigate the structural transformations of 2D silicon nanosheets under compression and decompression, showing the irreversible formation of 1D silicon nanowires.